Design and application of wireless network optimal data sharing architecture - Rupeng XU; Jingye CUI; Zeluo GUAN; Jing NING; Gang RU; Lei NIE; Zhiliang CHEN (Dianxin kexue)
During wireless network optimization，a variety of network data would be used. However，the presence of dispersed storage，low utilization rate and inconvenience in using and other issues of existing data are incapable of meeting the future needs of large data network optimization.Referring from the big data technology widely used in internet field，network optimization center，an architecture design of network optimization big data sharing platform was proposed，dispersed data was intergrated，and a unified data sharing port was formulated，which could utilize efficiency of data usage. Moreover，the sharing platform is able to support interoperability between software of computer and applications of telephone，which provides convenience for network optimization，consequently increase efficiency and quality of network optimization.